2019
DOI: 10.1002/lary.28045
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA‐103 promotes nasopharyngeal carcinoma through targeting TIMP‐3 and the Wnt/β‐catenin pathway

Abstract: Objectives/Hypothesis To verify how microRNA‐103 (miR‐103) is involved in nasopharyngeal carcinoma (NPC) development. Study Design Research on the relationship between miR‐103 and NPC. Methods Tissue inhibitor of metalloproteinases‐3 (TIMP‐3) was identified as the theoretical target gene of miR‐103, and its regulatory mechanism in NPC was explored by quantitative reverse transcription polymerase chain reaction, Western blot, MTT, transwell, and luciferase reporter assays. Results MiR‐103 was upregulated wherea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 32 publications
1
6
0
Order By: Relevance
“…Herein, our results illustrated that TIMP3 methylation levels were augmented and TIMP3 protein levels were suppressed in C666-1 and C666-1R cells, with C666-1R cells showing the more obvious alteration; meanwhile, after miR-613 overexpression, TIMP3 methylation levels were suppressed, and TIMP3 protein levels were facilitated in C666-1R cells, whereas further DNMT3B overexpression reversed the above trends in C666-1R cells. Consistent lowly expressed TIMP3 was previously reported in NPC tissues [42], while knockdown of TIMP3 methylation was associated with alleviation of breast cancer [34]. In short, these findings and data make it plausible to suggest that miR-613 reduces TIMP3 methylation levels by inhibiting DNMT3B.…”
Section: Disease Markerssupporting
confidence: 85%
See 2 more Smart Citations
“…Herein, our results illustrated that TIMP3 methylation levels were augmented and TIMP3 protein levels were suppressed in C666-1 and C666-1R cells, with C666-1R cells showing the more obvious alteration; meanwhile, after miR-613 overexpression, TIMP3 methylation levels were suppressed, and TIMP3 protein levels were facilitated in C666-1R cells, whereas further DNMT3B overexpression reversed the above trends in C666-1R cells. Consistent lowly expressed TIMP3 was previously reported in NPC tissues [42], while knockdown of TIMP3 methylation was associated with alleviation of breast cancer [34]. In short, these findings and data make it plausible to suggest that miR-613 reduces TIMP3 methylation levels by inhibiting DNMT3B.…”
Section: Disease Markerssupporting
confidence: 85%
“…Reduced TIMP3 Methylation by Inhibiting DNMT3B. TIMP3 was previously established to be lowly expressed in NPC tissues [42], and TIMP3 methylation is a common occurrence in many cancers [34,43,44]. DNMT3B further represents a major DNA methyltransferase regulated by miR-613.…”
Section: Mir-613mentioning
confidence: 99%
See 1 more Smart Citation
“…In vitro experiments revealed that miR‐103 regulates the late stages of autophagy in human keratinocytes 19 . Additionally, an increasing number of reports outlined the involvement of miR‐103 in the proliferation, migration, invasion, and apoptosis of tumour cells 20,21 . It was believed that wound healing and tumours were similar in molecular and functional mechanisms 22 .…”
Section: Introductionmentioning
confidence: 99%
“…29,30 Tissue inhibitor of metalloproteinase-3 (TIMP3), located on chromosome 22q12, is an endogenous inhibitor of protease activity. 31 Interestingly, TIMP3 can be regulated by many miRNAs in cancers, including miR-103 in nasopharyngeal carcinoma (NPC), 32 miR-21 in HCC 33 and miR-17-5p in bladder cancer. 34 More importantly, accumulating evidence has indicated that TIMP3 also affects the tumorigenesis of HCC.…”
Section: Introductionmentioning
confidence: 99%